Vegetarian diet effects on somatic parameters in Rattus norvegicus and hematological variety Sprague Dawley - Maria del Pilar Ramos Vizcardo (2020)
The present work aimed to establish the effects of two different diets, omnivorous and vegetarian, on somatic, hematological parameters in laboratory rats. It was carried out in the Bioterio and Laboratory of Animal Physiology of the Department of Biology of the UNSA, Arequipa, during the months April to November of 2017. 24 Rattus norvegicus laboratory rats were used, assigned to two groups that were subjected to “onmivorous” and “vegetarian” diets, respectively for 120 days (4 months) where somatic parameters (body weight, total length and tail length were analyzed), erythron (corpuscular volumes VCM, HCM, CHCM) leukocyte indices (I. Schilling, I. Arneth, IN, IG, IR in Rattus norvegicus variety Sprague Dawley and hemostasis (platelet count and prothrombin time) in Rattus norvegicus variety Sprague Dawley. Body weight and length rose similarly in both groups. The length of the tail in both groups rose similarly in both groups but in the evaluation times, 30, 60 and 120 days, the length had greater development in the omnivorous group (p <0.05). The erythron tends to rise in the omnivore. The RL does not suffer significant variations. The percentage of lymphocytes tend to rise in both groups.